A qualitative investigation of young people’s experiences and views of Early Support Hubs across England - Lily Wright; Jessica L. Griffiths; Rebecca Appleton; Sadiya Begum; Connor Clarke; Nima Cas Hunt; Hannah Kate Lewis; Phoebe Barnett; Anam Bhutta; Eva Driskell; Julian Edbrooke-Childs; Andrew Grundy; et al. (PLoS ONE, 2026)
Background Youth is a period of elevated risk for mental ill health, yet young people often do not receive timely support. Barriers can include high clinical thresholds for treatment and long waiting lists, as overstretched statutory services can struggle to meet high demand. The Early Support Hubs available in some parts of England are a potentially promising model to increase access to support. These are community-based services offering open-access, holistic support for 11–25-year-olds without a referral. However, there is no standardised model and considerable variation in the support offered, highlighting the need for research to explore how Early Support Hubs operate, whether they are meeting the mental health and wellbeing needs of young people, and potential areas for improvement. Aims To explore young people’s experiences of using Early Support Hubs for mental health or wellbeing support, and their views on best practice within these services. Methods We conducted semi-structured interviews with 20 demographically diverse young people aged 16–25 years who had used eight Early Support Hub services across England. Data were analysed using codebook thematic analysis. Results Aspects of hubs that were valued by young people included: easy accessibility; holistic approaches which go beyond clinical interventions; a sense of community, friendship and consistency; and youth-led philosophies. Limitations of the hub model included them being little known in local areas, lack of capacity to address more acute and complex mental health needs, and the limited scale of the services. Conclusion Early Support Hubs appear to be valued by young people and have potential to be an adjunct to clinical services to help increase access to mental health support for young people. Evidence on populations served, what support they receive, and outcomes following support are needed to assess whether there is a policy case for wider roll out.